Record‐Breaking Increases in Arctic Solar Ultraviolet Radiation Caused by Exceptionally Large Ozone Depletion in 2020 - Bernhard, Germar H.; Fioletov, Vitali E.; Grooß, Jens‐Uwe; Ialongo, Iolanda; Johnsen, Bjørn; Lakkala, Kaisa; Manney, Gloria L.; Müller, Rolf; Svendby, Tove (Geophysical Research Letters, 2020)
Measurements of solar ultraviolet radiation (UVR) performed between January and June 2020 at 10 Arctic and subarctic locations are compared with historical observations. Differences between 2020 and prior years are also assessed with total ozone column and UVR data from satellites. Erythemal (sunburning) UVR is quantified with the UV Index (UVI) derived from these measurements. UVI data show unprecedently large anomalies, occurring mostly between early March and mid‐April 2020. For several days, UVIs observed in 2020 exceeded measurements of previous years by up to 140%. Historical means were surpassed by more than six standard deviations at several locations in the Arctic. In northern Canada, the average UVI for March was about 75% larger than usual. UVIs in April 2020 were elevated on average by about 25% at all sites. However, absolute anomalies remained below 3.0 UVI units because the enhancements occurred during times when the solar elevation was still low.